(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This study aims to test the impact of stock liquidity portfolios on estimated returns using the CAPM capital asset pricing model, and was applied to a sample of 17 companies listed on the Damascus Securities Market during 2010-2020, by verifying that the most traded (and thus the most liquid) stocks yield higher returns. In addition to a test as there has been an impact on the stock returns of companies in the Damascus Securities Market, various liquidity measures are as follows: Turnover measure The turnover rate, liquidity scale according to Trade-volume trading volume, market value measure and size) ), liquidity ratio (AMIVEST), liquidity ratio AMIHUD, Zero Return zero returns, The equation of the CAPM model was used to estimate stock returns, The relationship between variables was tested using the simple regression equation after the companies’ shares were arranged according to their upward liquidity, and four portfolios of corporate shares were created based on each liquidity measure individually. The results indicated that liquidity is an important factor in pricing stock returns and that the most traded stocks (and thus more liquid stocks) yield higher returns, and also the effect of liquidity on the return varies according to the liquidity index used in the calculation.